Analysis of Competitive Anxiety Levels of Junior Hockey Athletes During the Pre-Competition Training Phase - Prasetia, Deslita Ayu; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi; Sopandi, Salma Maharani (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2026)
Competitive anxiety is a psychological factor that plays a significant role in influencing athlete performance, including in hockey. During the training phase, athletes’ anxiety needs to be considered because it can impact their mental preparedness for matches. This study aims to analyze the competitive anxiety levels of hockey athletes aged 17-20 years during the training phase. This study used a descriptive, quantitative, cross-sectional design. The subjects were 24 hockey athletes from Bandung City. The instrument used in this study was the Competitive State Anxiety Inventory-2 (CSAI-2R) questionnaire, which was administered once during the training phase. Data were analyzed using descriptive techniques, with means ± 1 standard deviation alongside an exploratory comparative analysis using an independent t-test to examine potential gender differences. The results showed that the athletes’ competitive anxiety levels were in the moderate category (mean = 40.88; SD = 6.265), with variations in scores on cognitive anxiety (mean = 11.88) and somatic anxiety (mean = 12.96) in the moderate category. In contrast, self-confidence showed the highest value (16.04). These findings indicate that athletes continue to experience psychological stress even during training. Hockey athletes’ competitive anxiety during the training phase is at a relatively manageable level but still requires attention in training programs. The results of this study recommend that coaches integrate mental training into their training programs, including stress management, self-confidence enhancement, and emotion regulation strategies, to help athletes manage anxiety and optimize their competitive readiness.